Dari Anarchic Cyber Space menjadi Transnational Public Sphere. Membaca Relasi antara Cyber¬ space fan Civil Society di Era Postmodern (Studi kasus: Greenpeace Online Activist) - Faisal, Moch (UI Scholars Hub, 2007)
This article tries to examine the relation between Cyberspace and Civil Society, especially in the post modem era. The writer believes that there is contestation amongst civil society, government, and private sector in order to dominate the public sphere. By using its apparatus, state is dominantly dominating public sphere in every day life. By using high technology and huge amount capital, private sector is successful in dominating public sphere especially in form of mass media. Private sector is much more profitable because by using mass media such television, private sector can dominate not only public sphere but also private sphere of society. Thus, where is civil society? Due to the lack of capital, civil society is being marginalized from public sphere. Even the number of NGO that is representing civil society is always increasing, in fact, the civic engagement is decreasing. Entering the post modem era which is signed by the rise of cyberspace, the condition is turn 180 degree. Cyberspace gives civil society the space to exist in public sphere. In one hand, cyberspace gives us space without any control and domination where all people free to express their self. In the other hand, it gives us an anarchist space that can not be controlled.